AB1344 Hospital infusion center costs for anti–tumor necrosis factor agents. (23rd January 2014) - Schmier, J.; Cifaldi, M.A.; Shaw, J.W.; Halpern, M.T.; Nickman, N.A.
Abstract : Background: Tumor necrosis factor (TNF)–inhibiting drugs are provided to patients with rheumatoid arthritis in the form of an intravenous infusion or subcutaneous injection. Although anti-TNF infusions are typically provided in hospital-based centers, the administrators of these centers often have limited understanding of the associated treatment costs. Objectives: To estimate the total cost of anti-TNF infusion care from a hospital perspective using an activity-based costing approach. Methods: An activity-based model was developed using several types of infusion center inputs: hourly wages, times to provide care, supply and overhead costs, laboratory test costs, infusion center size, and practice pattern information. The model assumed 8 infusions of infliximab annually. Base case values were derived from a survey of 5 community hospital infusion centers, previously published nurse and pharmacist time estimates, and expert opinion. Costs were derived from standard national sources. An overhead charge of 29.5% was applied to all costs. All costs were measured in or inflated to 2011 US dollars. Results: The total cost per infusion, including drug and laboratory costs, was estimated to be 3185. Most of this cost was attributable to the acquisition cost of the infused medication. Of the 427 not associated with drug, 93 was associated with recommended laboratory tests. Infusion costs—including labor and supplies associated with preparation, administration, and premedication and treatment of adverse events if necessary—were estimated at 334 per infusion. Of this amount, 121 was attributable to nonlabor categories (eg, capital equipment) and management (eg, inventory and documentation). In contrast, total Medicare reimbursement for a 3-hour infusion would be less than 120. A separate module including indirect costs (ie, lost productivity of patient and/or caregiver, transportation) estimated each infusion visit to be associated with an additional 146 cost to the patient. Conclusions: Although drug costs contribute most to the cost of anti-TNF infusion care, personnel, supply, and overhead costs can also be substantial. The model developed in this research can be used to quantify the total cost of providing anti-TNF infusion services so that financially responsible treatment strategies can be implemented at a given institution. In a market in which reimbursement and the efficient use of personnel are keenly important, such a tool can help hospital administrators make informed choices about the services to be offered and their financial implications. Disclosure of Interest: J. Schmier Employee of: Exponent, which received a research grant from Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott, J. Shaw Shareholder of: Abbott, Employee of: Abbott, M. Halpern Grant/Research support from: Abbott, N. Nickman Consultant for: Exponent, which received a research grant from Abbott